Agrobacterium-mediated transformation of the endophytic fungus Acremonium implicatum associated with Brachiaria grasses - Abello, J.F.; Kelemu, Segenet; García, C. (Elsevier, 2008)
Acremonium implicatum is a seed-transmitted endophytic fungus that forms symbiotic associations with the economically significant tropical forage grasses, Brachiaria species. To take advantage of the endophyte's plant protective properties, we developed an efficient Agrobacterium-mediated transformation system for Acremonium implicatum, using green fluorescent protein (GFP) expression and vector pSK1019 (trpC promoter) or pCAMBIA1300 (CaMV35S promoter). We found that transformation efficiency doubled for both mycelial and conidial transformation as the co-cultivation period for Agrobacterium tumefaciens and Acremonium implicatum was increased from 48 to 72 h. Significantly, optimal results were obtained for either mycelial or conidial transformation with Agrobacterium tumefaciens strain AGL-1 and vector pSK1019 under the control of the trpC promoter. However, mycelial transformation consistently generated a significantly higher number of transformants than did conidial transformation. The mitotic stability of the transferred DNA was confirmed by growing ten transformants in liquid and agar media for six generations. In all cases, resistance to the selection pressure (hygromycin B) was maintained. Fluorescence emission was retained by the transformants and also expressed in Brachiaria tissues from plants inoculated with GFP-transformed A. implicatum. This technology will help in the transfer and expression of agronomically important genes in host plants.